DIFFERENT CHARACTERISTICS BRAKE AUTOMOTIVE SYSTEM SALES RESEARCH MANUFACTURED BY ADDITIVE TECHNOLOGIES - Nesterenko, Mykola; Virchenko, Viktor; Shapoval, Mykola; Shokalo, Artem (Academic journal Industrial Machine Building Civil Engineering, 2019)
Problems in designing hydraulic brake systems of cars have been analyzed. The study of the braking process has conducted considering the distribution of forces on the axles during braking. The general support model research and support geometric characteristics are developed. The calculation of the car brake system has been conducted that enables to determine the load on the caliper during the braking process and using graphic dependencies, and to determine the concentration of maximum stresses in the mounting areas of the support. Based on analytical studies in the Autodesk Fusion 360 3D Modeling program, a design has been implemented that features a smaller metal capacity at the expense of rational design and providing uniform strength across the entire surface. Adaptive technologies also significantly accelerate the production of new parts due to the lack of need for the production of auxiliary equipment, such as molds.